1996
DOI: 10.1111/j.1476-5381.1996.tb15605.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct chronotropic effects of atrial and C‐type natriuretic peptides in anaesthetized dogs

Abstract: 1 The chronotropic effects of atrial natriuretic peptide (ANP) and C-type natriuretic peptide (CNP) were investigated using injections (50 Mg in 1 ml of Tyrode solution as bolus over 1 min) directly into the sinus node artery of 21 anaesthetized and vagotomized dogs which had been pretreated with a f,-adrenoceptor antagonist. The injections were also repeated following: (a) a-adrenoceptor antagonism (prazosin) and muscarinic receptor antagonism (atropine); (b) inhibition of prostaglandin synthesis (indomethac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
(60 reference statements)
0
8
0
1
Order By: Relevance
“…These effects were shown to be dependent on activation of NPR-C and were only seen in the presence of a saturating dose (1 μM) of the β-adrenergic receptor (β-AR) agonist isoproterenol (ISO). On the other hand some studies have shown that NPs can increase HR and/or SAN activity in vivo and/or in isolated atrial preparations [12][13][14]. These variable responses may be related to a lack of understanding of how different NPRs contribute to physiological responses in different conditions.…”
Section: Introductionmentioning
confidence: 93%
“…These effects were shown to be dependent on activation of NPR-C and were only seen in the presence of a saturating dose (1 μM) of the β-adrenergic receptor (β-AR) agonist isoproterenol (ISO). On the other hand some studies have shown that NPs can increase HR and/or SAN activity in vivo and/or in isolated atrial preparations [12][13][14]. These variable responses may be related to a lack of understanding of how different NPRs contribute to physiological responses in different conditions.…”
Section: Introductionmentioning
confidence: 93%
“…In the rat and human heart, the three natriuretic receptor mRNAs were found (Nunez et al, 1992). Recently, Beaulieu et al (1996) and Hirose et al (1998) reported, respectively, direct chronotropic and dromotropic eects of CNP on anaesthetized dogs. While some studies show that ANP decreases contractility in isolated cardiomyocytes (Neyses & Vetter, 1989;McCall & Fried, 1990), the role of natriuretic peptides in the regulation of cardiac contractility has not been clearly established.…”
Section: Introductionmentioning
confidence: 98%
“…In the rat and human heart, the three natriuretic receptor mRNAs were found (Nunez et al ., 1992). Recently, Beaulieu et al . (1996) and Hirose et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a regulatory function of CNP has been recognized in the heart, i.e., CNP-induced positive chronotropic (1,2,14) and inotropic (2,14) effects in the dog heart. The natriuretic peptide family (11,29,46) and their specific receptors (2,8,33) have been demonstrated in the cardiac atria.…”
mentioning
confidence: 99%